Evaluate the Total Mechanical Gastroesophageal Anastomosis for Carcinoma Esophagus - Khan, Muhammad Abid; Aslam, Tahir; Ahmed, Asif; Aslam, Viqar; Tahir, Imran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate total mechanical gastroesophageal anastomosis in patients with carcinoma of esophagus. Study Design: Cross sectional study. Place and Duration of Study: Department of Surgery, Bolan Medical University, from Jan 2020 to Jun 2021. Methodology: Total of 75 patients were included consecutively in this observational cross sectional study involving patients diagnosed with esophageal cancer and awaiting to undergo esophagiectomy with mechanical anastomosis in-between 18 to 60 years and were ASA I and II were included. Patients that were ASA III or IV and having any systemic disorder and those that refused to participate were excluded. SPSS version 23.0 was used for data analysis keeping p-value <0.05 as significant. Results: Mean age of patients was 58.31 ± 6.2 years wherein 42(56%) males and 33(44%) females. 29 (38.7%) of patients were ASA I while 46 (61.3%) were ASA II. Mean operative time of patients was 240 ± 65.2 minutes while mean blood loss was 205 ± 32.3 ml. Regarding anastomotic leakage, minor (type I) leakage was observed in 05(6.7%) of patients while major (type II or III) leakage was seen in 03(4%) of patients. Anastomotic dilatation, stricture formation and death were reported in 01(1.33%) patient each. Conclusion: Total mechanical gastro-esophageal anastomosis was found to have safe, less time consuming and with minimal post-operative anastomotic leakage or stricture formation and morbidity.